The Successful Treatment of Obstructive Uropathy Caused by Retroperitoneal Fibrosis with Steroids in the Latent Tuberculosis Case - Soyoral, Yasemin; Ozbay, Bulent; Begenik, Huseyin; Aldemir, Mehmet Naci; Erkoç, Reha; Bulut, Deniz (Journal of Diagnostics, 2015)
Retroperitoneal fibrosis (RPF) is a rare disorder manifested by fibrosis and chronic inflammation in the retroperitoneal tissue. It has been reported that retroperitoneal fibrosis is induced by tuberculosis infection (4). We wanted to present a case of latent tuberculosis, who presented with anuria and developed by bilateral hydronephrosis depending on idiopathic RPF, and treated with steroid therapy, since it is a rare case.